WORK-ABILITY AND MOTIVATION'S IMPACT ON CIREBON EMPLOYEE PERFORMANCE - Fitriyah Fitriyah; Siti Maryam; Sandi Nasrudin Wibowo (SEAN Institute, 2023)
The main problem at PT. Dock & Shipping Kodja Bahari (Persero) Galangan Cirebon can be known to perform poorly, this is due to several obstacles such as not achieving project targets that must be completed. The target in question is for example there is a ship that wants to repair its ship, before the ship makes repairs there is a work contract that has been agreed upon by the ship that wants to be repaired and ship repair will be completed within a few weeks or months, for that employees in the production department are required to complete the work according to the agreed time. However, the results are less than optimal in doing work and the many competitors that can make customers divided, and result in customer employees switching to the company so that they can benefit these customers. This has not achieved employee targets. This research aims to determine the effect of work-ability and motivation Employee Performance totalling 67 people. The sampling technique used was non-probability sampling using saturated samples, so all population employee were sampled in this research. The data collection technique used a questionnaire, and the data analysis used was multiple linear regression analysis Thisis research indicates that work-ability has a positive and significant effect on employee es performance seen frothe m t count > t table, namely 5.613 > 1.997. Motivation has a positive and significant effect on employee performance, seen from tcount > ttable, namely 6.168 > 1.997. Simultaneously the variables of work-ability and motivation have a positive and significant impact on employee performance seen from the value of Fcount > Ftable, namely 68,816 >3.14. All the research, results both partially and simultaneously have a